The influence of the kinetic duties accompanying the method of scheduling lab serial and random in learning skilled football performance - Mohammed Nuhad, Tariq (International Journal of Psychosocial Rehabilitation, 2020)
The emergence of a positive effect of the experimental method is used according to the serial numbers and indiscriminate exercises in kinetic duties. There are moral differences between the results of the tests, for the benefit of the tribal and expose assessments tests (37484536). learn some football skills in the tests under study. There is a difference in the level of learning for some of the skills of football, the first experimental Group (serial exercises in kinetic duties), the second group (random exercises in kinetic duties) and the officer, according to the methods used in the search. Work to benefit from the results of the study using serial and indiscriminate exercises in kinetic duties—under discussion. To improve the performance level, skilled. Focus on random exercises in the manner of the duties, skills and mobility and open. Similar studies on other samples, different categories and ages to make sure of the validity of the findings of the study in other games.